“(Dis)Connections at the fundão in Greater Lisbon: the ambiguity of the place and not always visible heterogeneity of music scene in Portugal" - Bialoborska, Magdalena (Beyond Planetary Apartheid – International Conference, 2018)
Taking as an example a kind of fundão/terraço – a place where musical and socializing events, organized and attended by Santomean living at Lisbon Metropolitan Area, occur – this presentation intends to introduce a reflection about the segregation of the musical scene in Lisbon, on the one hand, and, on the other hand, contribute to the debate about the place/importance/character of the cultural practices of the African diaspora in Portugal. Visiting two places (situated in Amadora and in Camarate), two of the very few spots where Santomean bands play alive regularly, one may wonder if this kind of apartheidisation is voluntary or involuntary, and this is the key question of this reflection. Taking into consideration the cultural citizenship as a process where power and inequality are at play in relation to mechanisms of marginalization and exclusion (Rosaldo, 2003) and the distinction between invited and invented places (Miraftab, 2006), the problem of belonging (Lovell, 1998) is analysed as one of many possible ways to find the answer for the initial interrogation.